Vascular-Rheological Properties of Blood in Hemorrhagic Vasculitis Occurring in Childhood and Adulthood - V.V. Gerasymenko; E.D. Yegudina; O.E. Chernyshova; O.V. Syniachenko (Zaslavsky O.Yu., 2016)
Background. As a result of the immune-inflammatory necrotic changes in the walls of arterioles and capillaries in patients with hemorrhagic vasculitis (HV) Henoch - Schönlein endothelial dysfunction of vessels occurs, contributing to violations of blood rheological properties and microcirculation. These processes depend on the age of patients, and in cases of onset of the disease in childhood and adulthood are unknown. Objective: to study vascular and rheological properties of blood serum in HV and to compare the indices with different age of the debut of the pathological process in the groups of patients. Material and methods. The study included 174 patients with HV (83 % men and 17 % women). In 92 patients, the disease made its debut in childhood (on average in 12 years old), and in 82 - in the adult (on average in 25 years old). I, II and III degree of activity of pathological process are set at a ratio of 1 : 2 : 2. Indicators of vascular endothelial function were investigated by immune-enzyme analysis and the adsorption-rheological properties of blood were assessed by computer tensiometry. Results. HV is accompanied by severe disorders of the blood vascular and rheological properties which are involved in the pathogenesis of lesions of skin (endothelin-1, surface tension), joints (only surface activity), kidney (prostacyclin, cyclic guanosine monophosphate) and heart (endothelin-1, viscoelastic modulus). At that the integrated indicators of vascular endothelial function, viscoelastic, surface-active and relaxation characteristics of serum depend on the age of the patients in the beginning of the disease, the degree of activity of the pathological process, the clinical form of the disease course, necrotic-ulcerative and polymorphic variants of cutaneous vasculitis, and HV, transforming from juvenile, occurs with lower blood levels of endothelin-1, but with a higher concentration of thromboxane A2, cyclic guanosine monophosphate and surface viscosity index. Conclusions. There are features of vascular changes of rheological properties of blood serum in HV begun in childhood and adulthood that distinguishes these groups of patients and in some links of the pathogenesis of the disease.